Solar cells, metallization pastes, photovoltaic modules and photovoltaic systems
Patent Information
- Application Number
- CN202611322788.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]有鉴于此,本发明所要解决的技术问题在于提供太阳能电池、金属化浆料、光伏组件及光伏系统,以克服现有技术中抗紫外诱导衰减方案主要依赖封装层面防护、存在紫外吸收剂易迁移降解、完全阻隔紫外光造成能量浪费、以及电池电极与钝化层/隧穿氧化层界面缺乏主动防护机制等技术缺陷,从而从电极端源头阻断紫外光损伤,在保障电池光电转换效率的同时提升光伏组件的长期可靠性
[0015]本发明提供的金属化浆料应用于太阳能电池中,可从电极-硅界面层面抑制紫外诱导衰减,同时适配电池钝化层/隧穿层。具体而言,太阳光入射后,280 nm~380 nm紫外光在到达电池界面之前,被含功能性物质电极层中的紫外屏蔽物质阻隔;经含功能性物质电极层作用后,大量紫外光无法到达电池钝化层/隧穿氧化层界面,避免紫外光导致界面缺陷生成、Si-H键断裂、载流子复合中心增加,从而从源头抑制紫外诱导衰减;同时,可见光可顺利穿透浆料间隙进入电池基体,保证电池光电转换效率不受影响。因此,本发明提供的金属化浆料应用于太阳能电池中,能够从电池电极端阻断紫外光损伤,突破传统仅依赖封装胶膜紫外防护的局限,实现抗紫外诱导衰减,进而提升光伏组件长期可靠性,并且发电效率能够得到保证。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cell technology, specifically to ultraviolet-induced degradation, conductive paste, ultraviolet light conversion, and ultraviolet absorption of solar cells, and more specifically to solar cells, metallization paste, photovoltaic modules, and photovoltaic systems. Background Technology
[0002] Ultraviolet-induced degradation (UVID) refers to the power degradation phenomenon that occurs in photovoltaic modules after long-term outdoor exposure to ultraviolet radiation. For solar cells, ultraviolet light has high photon energy, and long-term exposure can adversely affect the passivation layer, tunneling oxide layer, and electrode contact interface on the cell surface, leading to power degradation. With the increasing requirements for the long-term reliability of photovoltaic modules, UVID has become one of the important factors affecting the long-term outdoor power generation performance of modules.
[0003] Currently, industry solutions for combating UV-induced degradation primarily focus on the encapsulation level. For example, adding UV absorbers to encapsulation films such as EVA and POE films, or using UV-blocking glass to block UV light. While these solutions can reduce the amount of UV light entering the module to some extent, their protection is mainly located within the encapsulation system outside the solar cell. Essentially, they remain passive protection solutions at the encapsulation end, lacking an active protection mechanism between the encapsulation film and the solar cell. UV light can still penetrate through gaps in the encapsulation film to the cell electrode interface, triggering UVID.
[0004] In addition, existing solutions for resisting UV-induced degradation still have the following shortcomings: First, adding UV absorbers to encapsulation films such as EVA and POE films will cause the UV absorbers to migrate and degrade over time, resulting in a gradual decrease in protective effect. Especially under high temperature, high humidity, and strong UV radiation environments, the insufficient stability of the UV absorbers will further weaken the protective effect of the encapsulation layer on the solar cells. Second, using UV-blocking glass to block UV light will completely block the UV light and prevent it from being effectively utilized. The 5% to 8% of solar UV energy wasted will not only fail to achieve power generation gains, but may also sacrifice some potential spectral utilization efficiency. Summary of the Invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide solar cells, metallization pastes, photovoltaic modules and photovoltaic systems to overcome the technical defects of existing anti-UV-induced degradation schemes, such as reliance on encapsulation layer protection, easy migration and degradation of UV absorbers, energy waste caused by complete blocking of UV light, and lack of active protection mechanism at the interface between battery electrodes and passivation / tunneling oxide layers. In this way, the present invention blocks UV damage from the source of the electrode, and improves the long-term reliability of photovoltaic modules while ensuring the photoelectric conversion efficiency of the battery.
[0006] In a first aspect, the present invention provides a solar cell, wherein at least one electrode of the solar cell comprises a functional material, the functional material comprising an ultraviolet shielding material, the ultraviolet shielding material comprising one or more of TiO2-SiO2 core-shell particles, ZnO-Al2O3 composite particles, and CeO2-doped TiO2 powder.
[0007] The solar cell provided by this invention has anti-UV-induced degradation functionality. Specifically, after sunlight incident, 280 nm to 380 nm UV light is blocked by a UV-shielding material before reaching the cell interface. A large amount of UV light cannot reach the passivation layer / tunneling oxide layer interface, preventing UV-induced interface defects, Si-H bond breakage, and an increase in carrier recombination centers, thus suppressing UV-induced degradation at its source. Simultaneously, visible light can smoothly enter the cell substrate, ensuring that the cell's photoelectric conversion efficiency remains unaffected. Therefore, the solar cell provided by this invention can block UV damage at the cell electrode, exhibiting anti-UV-induced degradation functionality. Photovoltaic modules made from this solar cell have long-term reliability, and their power generation efficiency can be guaranteed.
[0008] The solar cell provided by this invention includes at least one electrode comprising a functional material. Specifically, the functional material accounts for 5% to 60% of the mass distribution of the electrode. The distribution structure of the functional material in the electrode according to this invention includes one of the following three distribution structures: ① the functional material is distributed on the side of the electrode that contacts the cell substrate of the solar cell; ② the functional material is distributed on the side of the light-receiving surface of the electrode; ③ the functional material is uniformly distributed in the electrode.
[0009] The functional material described in this invention includes an ultraviolet (UV) shielding material, wherein the UV shielding material has a UV shielding efficiency of ≥95% in the 280 nm to 380 nm wavelength band. In one embodiment of this invention, the D50 particle size of the UV shielding material is 30 nm to 250 nm.
[0010] Preferably, the functional substance of the present invention further includes a functional protective agent; wherein the functional protective agent includes one or more of ultraviolet absorbers and ultraviolet light-converting agents. Preferably, the ultraviolet absorber includes one or more of benzophenones, benzotriazoles, triazines, cyanoacrylates, salicylates, and polymeric ultraviolet absorbers. In some embodiments of the present invention, the ultraviolet absorber includes one or more of UV-531, 2,2-dihydroxybenzophenone, UV-P, UV-327, UV-329, UV-1577, UV400, BASF T479, and UV-3035.
[0011] Preferably, the ultraviolet conversion agent comprises a thermally activated delayed fluorescence (TADF) organic conversion agent and a rare earth phosphor; the emission peak of the TADF organic conversion agent is located at 450 nm to 520 nm, and the emission peak of the rare earth phosphor (such as europium / terbium-doped aluminate) is located at 500 nm to 550 nm. Alternatively, the ultraviolet conversion agent comprises one or more of coumarin derivatives, naphthalimides, and perovskite quantum dots.
[0012] The electrode of the present invention further includes an electrode substrate, which is one or more of silver, silver-coated copper, silver-coated aluminum, and copper, preferably silver; the electrode substrate accounts for 40% to 95% of the mass distribution in the electrode; the electrode substrate is uniformly distributed in the electrode. More preferably, the electrode substrate includes a first conductive powder and a second conductive powder in a mass ratio of (6 to 9): 1, wherein the first conductive powder is a flake-shaped conductive powder with a diameter of 3 μm to 8 μm, and the second conductive powder is a spherical conductive powder with a D50 particle size of 0.5 μm to 2 μm or a nano-conductive powder with a D50 particle size of 50 nm to 200 nm. More preferably, the electrode substrate includes a first silver powder and a second silver powder in a mass ratio of (6 to 9): 1, wherein the first silver powder is a flake-shaped silver powder with a diameter of 3 μm to 8 μm, and the second silver powder is a spherical silver powder with a D50 particle size of 0.5 μm to 2 μm or a nano-silver powder with a D50 particle size of 50 nm to 200 nm.
[0013] In some embodiments of the present invention, the solar cell provided by the present invention specifically includes a cell substrate and an electrode disposed on the surface of the cell substrate. The electrode has a double-layer structure, including a functional material electrode layer and an electrode layer disposed on the light-receiving surface of the functional material electrode layer. The functional material electrode layer includes a functional material; the functional material is the same as described above and will not be repeated. The solar cell of the present invention includes at least one of TOPCon cells, HJT cells, BC cells, perovskite / tandem cells, etc.
[0014] Secondly, the present invention provides a metallizing paste, which comprises the following components by mass percentage: 70%~85% conductive material; 2%~8% functional material; 10%~22% organic carrier; 0.2%~0.8% interface compatibilizer; and 0.3%~1.2% additives. The functional material includes an ultraviolet shielding material, which is the same as described above and will not be repeated here.
[0015] The metallization paste provided by this invention, when applied to solar cells, can suppress UV-induced degradation at the electrode-silicon interface level, while also being compatible with the cell passivation / tunneling layer. Specifically, after sunlight incident, 280 nm to 380 nm UV light is blocked by the UV-shielding material in the functional electrode layer before reaching the cell interface. After being acted upon by the functional electrode layer, a large amount of UV light cannot reach the cell passivation / tunneling oxide layer interface, preventing UV light from causing interface defects, Si-H bond breakage, and an increase in carrier recombination centers, thereby suppressing UV-induced degradation at its source. Simultaneously, visible light can smoothly penetrate the paste gaps into the cell substrate, ensuring that the cell's photoelectric conversion efficiency remains unaffected. Therefore, the metallization paste provided by this invention, when applied to solar cells, can block UV damage from the cell electrode, overcoming the limitations of traditional methods that rely solely on encapsulating films for UV protection, achieving resistance to UV-induced degradation, thereby improving the long-term reliability of photovoltaic modules and ensuring power generation efficiency.
[0016] The functional material of this invention preferably comprises an ultraviolet shielding material and a functional protective agent in a mass ratio of (15~25):1, more preferably (19~21):1, and even more preferably 20:1; the functional protective agent is the same as described above and will not be repeated. In some embodiments of this invention, the functional material comprises an ultraviolet shielding material, a functional protective agent, and a solvent, wherein the ultraviolet shielding material comprises 0.1%~5% by mass in the functional material. In some embodiments of this invention, the ultraviolet conversion agent in the functional protective agent preferably comprises a thermally activated delayed fluorescence organic conversion agent and a rare earth phosphor in a mass ratio of 1:(2~4).
[0017] The metallization paste of the present invention includes a conductive material, which is selected from one or more of silver powder, silver-coated copper powder, silver-coated aluminum powder, and copper powder, preferably silver powder. More preferably, the conductive material includes a first conductive powder and a second conductive powder in a mass ratio of (6~9):1; wherein the first conductive powder is a flake-shaped conductive powder with a diameter of 3 μm to 8 μm, and the second conductive powder is one or more of spherical conductive powder with a D50 particle size of 0.5 μm to 2 μm or nano-conductive powder with a D50 particle size of 50 nm to 200 nm. More preferably, the conductive material includes a first silver powder and a second silver powder in a mass ratio of (6~9):1, wherein the first silver powder is a flake-shaped silver powder with a diameter of 3 μm to 8 μm, and the second silver powder is a spherical silver powder with a D50 particle size of 0.5 μm to 2 μm or nano-silver powder with a D50 particle size of 50 nm to 200 nm.
[0018] The metallization slurry of this invention includes an organic carrier. Specifically, the organic carrier includes a resin and an organic solvent. Preferably, the resin includes one or two of ethyl cellulose, acrylic resin, and polyurethane resin; the organic solvent includes one or two of terpineol, butyl carbitol, and diethylene glycol monobutyl ether. In some embodiments of this invention, the resin includes a first resin and a second resin in a mass ratio of (1~3):1, wherein the first resin and the second resin independently include ethyl cellulose, acrylic resin, or polyurethane resin, and the first resin and the second resin are not the same. Preferably, the resin includes ethyl cellulose and acrylic resin in a mass ratio of 1:1. In some embodiments of this invention, the organic solvent includes a first organic solvent and a second organic solvent in a volume ratio of (1~3):1, wherein the first organic solvent and the second organic solvent independently include terpineol, butyl carbitol, or diethylene glycol monobutyl ether, and the first organic solvent and the second organic solvent are not the same. Preferably, the organic solvent includes terpineol and diethylene glycol monobutyl ether in a volume ratio of 2:1.
[0019] The metallization slurry of this invention includes an interface compatibilizer. Specifically, the interface compatibilizer includes one or more of silane coupling agents, titanate coupling agents, aminosilanes, polysilazane derivatives, or phosphorus-containing passivators. Preferably, if the metallization slurry is applied to HJT batteries, the interface compatibilizer can be KH-570, which is suitable for amorphous silicon surfaces; if the metallization slurry is applied to TOPCon batteries, the interface compatibilizer can be KH-560, which is suitable for tunneling oxide layers; if the metallization slurry is applied to PERC batteries, the interface compatibilizer can be the titanate coupling agent NDZ-101. The specific examples given above are merely illustrative and not the only possible solutions.
[0020] The metallization slurry of the present invention includes additives, namely a thixotropic agent, an anti-settling agent, and glass powder. Specifically, the additives include 0.1%~0.8% thixotropic agent, 0.03%~0.5% anti-settling agent, and 0.1%~1.0% glass powder. The thixotropic agent is preferably selected from one or more of fumed silica or bentonite. The anti-settling agent is preferably selected from one or more of polycarboxylate or phosphate. The specific examples given above are merely illustrative and not the only possible solutions. The glass powder is preferably one or more of borosilicate glass, lead borosilicate glass, or low-melting-point bismuth-based glass; the D50 of the glass powder is preferably 0.5 μm~8 μm; the melting point of the borosilicate glass is 500℃~800℃; the melting point of the lead borosilicate glass is 400℃~800℃; and the melting point of the low-melting-point bismuth-based glass is 260℃~330℃.
[0021] Thirdly, the present invention provides a photovoltaic module, comprising: a solar cell as described in any of the above descriptions.
[0022] Fourthly, the present invention also provides a photovoltaic system, including the photovoltaic module as described above.
[0023] This invention provides solar cells, metallized paste, photovoltaic modules, and photovoltaic systems. The solar cells provided by this invention, based on electrodes formed from the metallized paste, can block ultraviolet light damage at the cell's electrode ends. Simultaneously, they are compatible with passivation / tunneling layers, improving the long-term reliability of the photovoltaic modules and ensuring power generation efficiency. The overall formulation of the metallized paste described in this invention is fully compatible with existing screen printing and high-temperature co-sintering processes, requiring no production line modifications. Experimental results using TOPCon cells as an example show that this invention can significantly reduce the degradation of key electrical parameters caused by ultraviolet irradiation, improving the long-term operational reliability of the cells. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the solar cell structure described in this invention;
[0025] Figure 2 This is an exploded view of the photovoltaic module described in this invention;
[0026] Figure 3 This is a schematic diagram of the battery string layer described in this invention;
[0027] Figure 4 This is a schematic diagram of the photovoltaic system described in this invention;
[0028] The accompanying drawings are not drawn to scale.
[0029] Figure label:
[0030] Figure 1 In the diagram, 1 is an electrode, 2 is the photovoltaic cell substrate, 3 is the contact surface between the functional electrode layer and the cell substrate, 11 is the electrode layer, and 12 is the functional electrode layer.
[0031] Figure 2 In the diagram, 100 is the front cover, 200 is the first encapsulation film, 300 is the battery string layer, 400 is the second encapsulation film, 500 is the back cover, 600 is the frame, and 700 is the junction box.
[0032] Figure 4 In the diagram, 1000 represents the module of the photovoltaic system, and 1010 represents the photovoltaic module. Detailed Implementation
[0033] The descriptions of specific structures or functions implemented according to the concept of this application disclosed in this specification are merely illustrative examples for explaining embodiments based on the concept of this application. Those skilled in the art will understand that embodiments based on the concept of this application can have various variations and forms, and are not limited to the embodiments described in this specification, but also include various modifications, equivalents, or substitutions made within the scope of the purpose, concept, and technology of this application.
[0034] In the description of this application, it should be understood that the use of terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" indicates the relative orientation or positional relationship between different components, and is only for the convenience of describing this application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.
[0035] Although the terms "first" or "second" may be used to describe various components or components, the components or components should not be limited by the terms. The terms above are used only for the purpose of distinguishing one component or component from another. For example, without departing from the scope of the claims according to the concept of this application, a first battery cell may be referred to as a second battery cell, and similarly, a second battery cell may be referred to as a first battery cell.
[0036] In this application, unless otherwise expressly specified and limited, the terms "connected," "fixed," "set," etc., should be interpreted broadly. For example, when one component is said to "connect" another component, it should be understood that it can be directly or indirectly connected to the other component, meaning that other components may also be present in between. Similarly, the terms "fixed" and "set" should be interpreted broadly in a similar way. Furthermore, the term "connected" can refer to a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can refer to the internal communication of two components or the interaction between two components, unless otherwise expressly limited. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances. In this application, unless otherwise expressly specified and limited, the description of "above" or "below" the second feature can mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, "above," "on top of," and "over" the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. The first feature being "below", "under", or "below" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0037] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings.
[0038] The researchers of this application have found that existing solutions for resisting UV-induced degradation still have the following shortcomings: First, adding UV absorbers to encapsulation films such as EVA and POE films will cause the UV absorbers to migrate and degrade over time, resulting in a gradual decrease in protective effect. Especially under high temperature, high humidity, and strong UV radiation environments, the insufficient stability of the UV absorbers will further weaken the protective effect of the encapsulation layer on the solar cells. Second, using UV-blocking glass to block UV light will completely block the UV light and prevent it from being effectively utilized. The wasted 5% to 8% of solar UV energy will not only fail to achieve power generation gain, but may also sacrifice some potential spectral utilization efficiency.
[0039] Based on this, the first aspect of the present invention provides a solar cell, wherein at least one electrode of the solar cell includes a functional material, the functional material including an ultraviolet shielding material, the ultraviolet shielding material including one or more of TiO2-SiO2 core-shell particles, ZnO-Al2O3 composite particles, and CeO2-doped TiO2 powder.
[0040] The solar cell provided by this invention has anti-UV-induced degradation functionality. Specifically, after sunlight incident, 280 nm to 380 nm UV light is blocked by a UV-shielding material before reaching the cell interface. A large amount of UV light cannot reach the passivation layer / tunneling oxide layer interface, preventing UV-induced interface defects, Si-H bond breakage, and an increase in carrier recombination centers, thus suppressing UV-induced degradation at its source. Simultaneously, visible light can smoothly enter the cell substrate, ensuring that the cell's photoelectric conversion efficiency remains unaffected. Therefore, the solar cell provided by this invention can block UV damage at the cell electrode, exhibiting anti-UV-induced degradation functionality. Photovoltaic modules made from this solar cell have long-term reliability, and their power generation efficiency can be guaranteed.
[0041] The solar cell provided by this invention includes at least one electrode comprising a functional material. Specifically, the functional material accounts for 5% to 60% of the mass distribution of the electrode. The distribution structure of the functional material in the electrode according to this invention includes one of the following three distribution structures: ① the functional material is distributed on the side of the electrode that contacts the cell substrate of the solar cell; ② the functional material is distributed on the side of the light-receiving surface of the electrode; ③ the functional material is uniformly distributed in the electrode.
[0042] The functional material described in this invention includes an ultraviolet (UV) shielding material, which has a UV shielding efficiency of ≥95% in the 280 nm to 380 nm wavelength range. The UV shielding material described in this invention is a core-shell, coated, or doped inorganic nanoparticle, which can effectively improve UV shielding stability. In one embodiment of this invention, the D50 particle size of the UV shielding material is 30 nm to 250 nm.
[0043] Preferably, the functional material of the present invention further includes a functional protective agent; wherein the functional protective agent includes one or more of ultraviolet absorbers and ultraviolet light converting agents. The specific examples given above are merely illustrative and not the only solution. After sunlight is incident, the 280 nm to 380 nm ultraviolet light is doubly blocked by the ultraviolet shielding material and the ultraviolet absorber before reaching the battery interface, or is blocked by the ultraviolet shielding material while being efficiently converted into 450 nm to 550 nm visible light by the ultraviolet light converting agent. This allows the ultraviolet light to be shielded / converted from the battery terminals, protecting the battery passivation layer / tunneling layer and adapting to different protection requirements.
[0044] Specifically, the ultraviolet absorber, as a shielding functional protective agent, can achieve ultraviolet absorption. Preferably, the ultraviolet absorber includes one or more of benzophenones, benzotriazoles, triazines, cyanoacrylates, salicylates, and polymeric ultraviolet absorbers. In some embodiments of the present invention, the ultraviolet absorber includes one or more of UV-531, 2,2-dihydroxybenzophenone, UV-P, UV-327, UV-329, UV-1577, UV400, BASF T479, and UV-3035. The specific examples given above are merely illustrative and not the only possible solutions.
[0045] The ultraviolet (UV) light-converting agent, as a light-converting functional protective agent, can convert UV light into visible light that the battery responds to, achieving a dual effect of protection and efficiency enhancement. Preferably, the UV light-converting agent includes a thermally activated delayed fluorescence (TADF) organic light-converting agent and a rare-earth phosphor; the emission peak of the TADF organic light-converting agent is located at 450 nm to 520 nm, and the emission peak of the rare-earth phosphor (such as europium / terbium-doped aluminate) is located at 500 nm to 550 nm. Alternatively, the UV light-converting agent includes one or more of coumarin derivatives, naphthalimides, and perovskite quantum dots. The specific examples given above are merely illustrative and not the only possible solutions.
[0046] The electrode of the present invention further includes an electrode substrate, which is one or more of silver, silver-coated copper, silver-coated aluminum, and copper, preferably silver; the electrode substrate accounts for 40% to 95% of the mass distribution in the electrode; the electrode substrate is uniformly distributed in the electrode. More preferably, the electrode substrate includes a first conductive powder and a second conductive powder in a mass ratio of (6 to 9): 1, wherein the first conductive powder is a flake-shaped conductive powder with a diameter of 3 μm to 8 μm, and the second conductive powder is a spherical conductive powder with a D50 particle size of 0.5 μm to 2 μm or a nano-conductive powder with a D50 particle size of 50 nm to 200 nm. More preferably, the electrode substrate includes a first silver powder and a second silver powder in a mass ratio of (6 to 9): 1, wherein the first silver powder is a flake-shaped silver powder with a diameter of 3 μm to 8 μm, and the second silver powder is a spherical silver powder with a D50 particle size of 0.5 μm to 2 μm or a nano-silver powder with a D50 particle size of 50 nm to 200 nm. This invention uses a blend of two conductive powders as the main electrode material, which can form an electrode conductive network, ensuring low contact resistance and high conductivity; the blend of sheet-like and spherical conductive powders further ensures conductivity and UV control.
[0047] In some embodiments of the present invention, the solar cell provided by the present invention has the following structural schematic diagram. Figure 1 As shown, Figure 1This is a schematic diagram of the solar cell structure described in this invention. Specifically, it includes a photovoltaic cell substrate 2 and an electrode 1 disposed on the surface of the photovoltaic cell substrate 2. The electrode 1 has a double-layer structure, including a functional material electrode layer 12 and an electrode layer 11 disposed on the light-receiving side surface of the functional material electrode layer 12. The functional material electrode layer 12 includes a functional material; the functional material is the same as described above and will not be repeated. The functional material electrode layer 12 of this invention is disposed on the surface of the photovoltaic cell substrate 2, so that the back-light side surface of the functional material electrode layer 12 is in direct contact with the surface of the photovoltaic cell substrate 2. The electrode layer 11 is disposed on the light-receiving side surface of the functional material electrode layer 12. The functional material electrode layer 12 directly protects the passivation layer / tunneling oxide layer, blocking ultraviolet light damage from the cell electrode. Simultaneously, it adapts to the cell passivation layer / tunneling layer, ensuring cell conversion efficiency and suppressing UVID, thus simultaneously improving reliability. The solar cell of this invention includes at least one of TOPCon cells, HJT cells, BC cells, perovskite / tandem cells, etc.
[0048] A second aspect of the present invention provides a metallization slurry, which comprises the following components by mass percentage: 70%~85% conductive material; 2%~8% functional material; 10%~22% organic carrier; 0.2%~0.8% interface compatibilizer; and 0.3%~1.2% additives. The functional material includes an ultraviolet shielding material, which is the same as described above and will not be repeated here. Furthermore, because it is a core-shell, coated, or doped inorganic nanoparticle, it effectively avoids the agglomeration of powder in the slurry system.
[0049] The metallization paste provided by this invention, when applied to solar cells, can suppress UV-induced degradation at the electrode-silicon interface level, while also being compatible with the cell passivation / tunneling layer. Specifically, after sunlight incident, 280 nm to 380 nm UV light is blocked by the UV-shielding material in the functional electrode layer 12 before reaching the cell interface. After the functional electrode layer 12 is activated, a large amount of UV light cannot reach the cell passivation / tunneling oxide interface, preventing UV light from causing interface defects, Si-H bond breakage, and an increase in carrier recombination centers, thereby suppressing UV-induced degradation at its source. Simultaneously, visible light can smoothly penetrate the paste gaps into the cell substrate, ensuring that the cell's photoelectric conversion efficiency remains unaffected. Therefore, the metallization paste provided by this invention, when applied to solar cells, can block UV damage from the cell electrode, overcoming the limitations of traditional methods that rely solely on encapsulating films for UV protection, achieving resistance to UV-induced degradation, thereby improving the long-term reliability of photovoltaic modules and ensuring power generation efficiency.
[0050] The functional material of this invention preferably comprises an ultraviolet shielding material and a functional protective agent in a mass ratio of (15~25):1, more preferably (19~21):1, and even more preferably 20:1; the functional protective agent is the same as described above and will not be repeated. In some embodiments of this invention, the functional material comprises an ultraviolet shielding material, a functional protective agent, and a solvent, wherein the mass fraction of the ultraviolet shielding material in the functional material is 0.1%~5%. The metallization paste of this invention contains an ultraviolet shielding phase and an ultraviolet absorbing / converting phase. After sunlight is incident, the 280 nm~380 nm ultraviolet light is doubly blocked by the ultraviolet shielding material and the ultraviolet absorber before reaching the battery interface, or is blocked by the ultraviolet shielding material while being efficiently converted into 450 nm~550 nm visible light by the ultraviolet converting agent. This suppresses ultraviolet-induced degradation at the electrode-silicon interface level, breaking through the limitations of traditional methods that rely solely on the ultraviolet protection of encapsulation films, and achieving resistance to ultraviolet-induced degradation.
[0051] The metallization paste of the present invention includes a conductive material, which is selected from one or more of silver powder, silver-coated copper powder, silver-coated aluminum powder, and copper powder, preferably silver powder. More preferably, the conductive material includes a first conductive powder and a second conductive powder in a mass ratio of (6~9):1; wherein the first conductive powder is a flake-shaped conductive powder with a diameter of 3 μm to 8 μm, and the second conductive powder is one or more of spherical conductive powder with a D50 particle size of 0.5 μm to 2 μm or nano-conductive powder with a D50 particle size of 50 nm to 200 nm. More preferably, the conductive material includes a first silver powder and a second silver powder in a mass ratio of (6~9):1, wherein the first silver powder is a flake-shaped silver powder with a diameter of 3 μm to 8 μm, and the second silver powder is a spherical silver powder with a D50 particle size of 0.5 μm to 2 μm or nano-silver powder with a D50 particle size of 50 nm to 200 nm. This invention uses a blend of two conductive powders as conductive materials. After the metallized paste forms the solar cell electrode, the conductive material can serve as the main electrode material, forming an electrode conductive network to ensure low contact resistance and high conductivity. The blend of sheet-like and spherical conductive powders further ensures conductivity and UV regulation.
[0052] The metallization paste of this invention includes an organic carrier that can disperse functional components, provide printability and film-forming properties, and is compatible with battery interfaces. Specifically, the organic carrier includes a resin and an organic solvent. Preferably, the resin includes one or two of ethyl cellulose, acrylic resin, and polyurethane resin; the organic solvent includes one or two of terpineol, butyl carbitol, and diethylene glycol monobutyl ether. In some embodiments of this invention, the resin includes a first resin and a second resin in a mass ratio of (1~3):1, wherein the first resin and the second resin independently include ethyl cellulose, acrylic resin, or polyurethane resin, and the first resin and the second resin are not the same. Preferably, the resin includes ethyl cellulose and acrylic resin in a mass ratio of 1:1. In some embodiments of this invention, the organic solvent includes a first organic solvent and a second organic solvent in a volume ratio of (1~3):1, wherein the first organic solvent and the second organic solvent independently include terpineol, butyl carbitol, or diethylene glycol monobutyl ether, and the first organic solvent and the second organic solvent are not the same. Preferably, the organic solvent includes terpineol and diethylene glycol monobutyl ether in a volume ratio of 2:1.
[0053] The metallization paste of this invention includes an interface compatibilizer, which can improve the interfacial adhesion and compatibility between the metallization paste and the battery cell / encapsulation film, thereby improving the stability of the paste-battery interface. Specifically, the interface compatibilizer includes one or more of silane coupling agents, titanate coupling agents, aminosilanes, polysilazane derivatives, or phosphorus-containing passivators. Preferably, if the metallization paste is applied to HJT batteries, the interface compatibilizer is KH-570, which is suitable for amorphous silicon surfaces; if the metallization paste is applied to TOPCon batteries, the interface compatibilizer is KH-560, which is suitable for tunneling oxide layers; if the metallization paste is applied to PERC batteries, the interface compatibilizer is the titanate coupling agent NDZ-101. The specific examples given above are merely illustrative and not the only possible solutions.
[0054] The metallization paste of this invention includes additives, including thixotropic agents, anti-settling agents, and glass powder, which can optimize printing accuracy, storage stability, enhance the sintering bond between the electrode and the battery cell, and reduce interfacial stress. Specifically, the additives include 0.1%~0.8% thixotropic agent, 0.03%~0.5% anti-settling agent, and 0.1%~1.0% glass powder. The thixotropic agent is preferably selected from one or more of fumed silica or bentonite. The anti-settling agent is preferably selected from one or more of polycarboxylate or phosphate. The glass powder is preferably one or more of borosilicate glass, lead borosilicate glass, or low-melting-point bismuth-based glass; the D50 of the glass powder is preferably 0.5 μm~8 μm; the melting point of the borosilicate glass is 500℃~800℃; the melting point of the lead borosilicate glass is 400℃~800℃; and the melting point of the low-melting-point bismuth-based glass is 260℃~330℃. The specific examples given above are merely illustrative and not the only possible solutions.
[0055] The preparation method of the metallized paste of the present invention includes the following steps: mixing functional substances, organic carriers, interface compatibilizers, additives and conductive substances to obtain metallized paste.
[0056] In some embodiments of the present invention, the functional substances in the metallization paste include ultraviolet shielding substances and functional protective agents, which are prepared by the following steps:
[0057] S1) The ultraviolet shielding material is mixed with an interface compatibilizer to carry out a surface modification reaction, thereby obtaining a modified ultraviolet shielding material;
[0058] S2) The functional protective agent dispersion and the modified ultraviolet shielding material are dispersed in an organic carrier containing additives and ground to obtain a functional slurry;
[0059] S3) The conductive material and the functional paste are mixed to obtain a metallized paste.
[0060] This invention first involves mixing a UV-shielding material with an interface compatibilizer to undergo a surface modification reaction, resulting in a modified UV-shielding material. Specifically, the UV-shielding material and the interface compatibilizer are subjected to a surface modification reaction in alcohol at 50°C to 80°C for 30 to 60 minutes to obtain the modified UV-shielding material. In some embodiments of this invention, the UV-shielding material and the interface compatibilizer are added to anhydrous ethanol at a mass ratio of 100:(1 to 10), and the surface modification reaction is carried out with stirring at 50°C to 80°C for 30 to 60 minutes. After filtration, the mixture is dried at 100°C to 150°C for 1 to 3 hours to obtain the modified UV-shielding material.
[0061] After obtaining the modified UV-shielding material, this invention disperses the functional protective agent dispersion and the modified UV-shielding material in an organic carrier containing additives, and then grinds them to obtain a functional slurry. Specifically, the functional protective agent dispersion and the modified UV-shielding material are shear-dispersed at high speed in an organic carrier containing additives, and ground until the slurry D90 ≤ 6 μm to obtain the functional slurry. In some embodiments of this invention, the modified UV-shielding material is added to an organic carrier containing additives, and stirred at high speed at 1200 rpm to 1800 rpm for 20 min to 40 min, then the functional protective agent dispersion is added and stirring is continued for another 20 min to 40 min, and then ground in a sand mill until the slurry D90 ≤ 6 μm to obtain the functional slurry.
[0062] In some embodiments of the present invention, the functional protective agent dispersion is prepared by the following steps: adding the functional protective agent to an organic solvent and ultrasonically dispersing it for 20 min to 30 min to obtain the functional protective agent dispersion; the organic carrier containing the auxiliary agent is prepared by the following steps: adding the resin to an organic solvent and stirring at 70°C to 95°C until completely dissolved, cooling to room temperature and adding the auxiliary agent, and stirring at a high speed of 1000 rpm to 1500 rpm for 30 min to 50 min to obtain the organic carrier containing the auxiliary agent.
[0063] After obtaining the functional slurry, the present invention mixes a conductive material with the functional slurry to obtain a metallized slurry. Specifically, the conductive material and the functional slurry are mixed, stirred at low speed, and degassed under vacuum to adjust the slurry viscosity to 60 Pa·s~120 Pa·s at 25°C and 10 rpm, thereby obtaining the metallized slurry. In some embodiments of the present invention, the conductive material is slowly added to the functional slurry, stirred at low speed of 300 rpm~500 rpm for 20 min~40 min, and degassed under vacuum of ≥0.08 MPa for 10 min~20 min, thereby adjusting the slurry viscosity to 60 Pa·s~120 Pa·s at 25°C and 10 rpm, thereby obtaining the metallized slurry.
[0064] The method for preparing the aforementioned solar cell of the present invention includes the following steps:
[0065] The metallization paste described above is printed onto the surface of the battery substrate and then co-sintered at high temperature to obtain a solar cell.
[0066] A third aspect of this invention provides a photovoltaic module, comprising: a solar cell as described in any of the above descriptions. The photovoltaic module of this invention is a device that directly converts light energy into electrical energy through the photoelectric effect or photochemical effect. A photovoltaic module is typically a stacked encapsulation structure, comprising at least: a front cover plate, a first encapsulating film, a cell string layer, a second encapsulating film, and a back cover plate from the light-facing side to the back-light-receiving side, as well as a frame surrounding the stacked structure and a junction box disposed on one side of the back cover plate. Figure 2 As shown, Figure 2 This is an exploded view of the photovoltaic module described in this invention.
[0067] The front cover can be made of a material with excellent light transmittance, impact resistance, corrosion resistance, and weather resistance, and may optionally include at least one of the following materials: tempered glass, plexiglass, transparent ceramics, organic fibers, or polymers. In some embodiments, the front cover may include at least one of an insulating barrier layer, a fluorinated weather-resistant layer, and a transition adhesive layer.
[0068] Back cover plates typically need to possess insulation, water resistance, aging resistance, weather resistance, and corrosion resistance. They can optionally include at least one of the following composite back covers as the substrate: tempered glass, acrylic glass, metal back cover, or PET film. The PET-based composite back cover can be selected from various types, such as composite (e.g., TPT / KPK, TPE / KPE), coated (e.g., TPC, KPC, CPC), and co-extruded (e.g., PO), depending on the needs of different scenarios.
[0069] Understandably, the choice of materials for the front cover and the back cover does not affect each other, and the same or different materials can be selected depending on the different application scenarios of the components (such as residential photovoltaics and building-integrated photovoltaics).
[0070] The first and second encapsulating films can be selected from at least one of ethylene-vinyl acetate copolymer (EVA) film, polyvinyl octene coelastomer (POE) film, EVA-POE-EVA co-extruded film (EPE), PVB (polyvinyl butyral), polyethylene terephthalate (PET) film, or liquid silicone. In some embodiments, the first and second encapsulating films may further include one or more functional additives selected from the group consisting of crosslinking agents, coupling agents, antioxidants, and ultraviolet absorbers to improve the degree of crosslinking, weather resistance, adhesive strength, and anti-aging properties of the films. It is understood that the first and second encapsulating films can be made of the same or different materials.
[0071] The battery string layer includes multiple battery strings, which can be combined in series, parallel, or series-parallel configurations to achieve current collection and output. Further, each battery string is formed by sequentially connecting multiple battery cells via connectors. In some embodiments, at least a portion of the connector is electrically connected to the back electrode of one battery cell, and at least another portion is electrically connected to the front or back electrode of another battery cell to form a battery string. The connector may optionally include conductive elements such as solder strips, busbars, or metal clips. In some embodiments, to improve welding performance, oxidation resistance, and weather resistance, the connector material may preferably be a highly conductive metal material, such as at least one of silver, copper, tin, and nickel, or an alloy thereof. In some embodiments, to balance conductivity and cost control, the connector material may also be at least one of metal-clad composite materials such as silver-coated copper, copper-coated silver, copper-coated aluminum, aluminum-coated copper, tin-plated copper, or nickel-plated copper. The electrical connection may be selected from one of the following methods: laser welding, spot welding, bonding, ultrasonic welding, resistance welding, or brazing. Figure 3 As shown, Figure 3 This is a schematic diagram of the battery string layer described in this invention.
[0072] The solar cell may include a semiconductor substrate, a first emitter of a first conductivity type, and a second emitter of a second conductivity type. It is understood that one of the first and second conductivity types is P-type, and the other is N-type. The semiconductor substrate may include an N-type silicon substrate or a P-type silicon substrate. N-type silicon substrates are typically formed by doping with Group V elements such as phosphorus, arsenic, or antimony, and have the characteristic that the majority charge carriers are electrons; P-type silicon substrates are typically formed by doping with Group III elements such as boron, gallium, or aluminum, and have the characteristic that the majority charge carriers are holes.
[0073] The solar cell can employ a grid line design with no main grid (OBB), multiple main grid (MBB), or super-multiple main grid (SMBB). In some embodiments, the grid line material can be selected as at least one of silver-based conductive paste or silver-coated copper composite paste. The paste uses highly conductive metal powder as the conductive substrate, and the substrate can be at least one of silver powder, copper powder, or silver-coated copper composite powder. To improve the ohmic contact performance, conductivity, and long-term weather resistance of the electrodes, a composite functional layer can be formed on the surface of the substrate or in the grid line structure. The functional layer material includes at least one of glass powder, organic carrier, nickel-based barrier layer, tin-based alloy layer, or anti-oxidation and corrosion-resistant coating.
[0074] It is understood that the solar cell can be at least one of the following commonly used in the field: TOPCon (Tunnel Oxide Passivated Contact) cell, HJT (Heterojunction with Intrinsic Thin-film) cell, BC (Back Contact) cell, perovskite / tandem cell, etc.
[0075] The frame surrounds the periphery of the stacked structure and is typically made of aluminum alloy or steel alloy. In some embodiments, the frame may also be a fiberglass frame or a plastic frame. The inner side of the frame usually has grooves for filling with sealant to achieve a sealed bond with the stacked components formed by the front cover, the first encapsulating film, the battery string layers, the second encapsulating film, and the back cover, thereby blocking moisture and buffering external impacts. In some embodiments, the frame can be assembled using corner brackets.
[0076] The junction box is located on one side of the rear cover and is electrically connected to the terminals of the bus electrodes in the battery string layer via a lead-out busbar for energy extraction. The junction box typically includes a housing and cover made of weather-resistant insulating material, conductive connecting tabs disposed within the housing, and one or more bypass diodes. The bypass diodes are connected in parallel with sub-units of the battery string. The electrical leads of the junction box include photovoltaic-specific connectors and cables. The cables preferably use cross-linked polyethylene insulation sheaths and tinned copper core wires. In some embodiments, the interior of the junction box may also be filled and encapsulated with potting compound to achieve insulation, thermal conductivity, moisture protection, and fixation.
[0077] A fourth aspect of the present invention provides a photovoltaic system, including the photovoltaic module as described above. Figure 4 As shown, Figure 4 This is a schematic diagram of the photovoltaic system described in this invention. The photovoltaic system described in this invention can be applied in photovoltaic power plants, such as ground-mounted power plants, rooftop power plants, and floating power plants, and can also be applied to equipment or devices that utilize solar energy to generate electricity, such as user solar power supplies, solar streetlights, solar cars, solar buildings, etc.
[0078] It is understandable that the application scenarios of photovoltaic (PV) systems are not limited to this; that is to say, PV systems can be applied in all fields that require solar energy for power generation. Taking a PV power generation system as an example, a PV system can include a PV array, a combiner box, and an inverter. The PV array can be an array combination of multiple PV modules; for example, multiple PV modules can form multiple PV arrays. The PV array is connected to the combiner box, which can collect the current generated by the PV array. The collected current flows through the inverter and is converted into AC power required by the mains power grid before being connected to the mains power grid to realize solar power supply.
[0079] The present invention will be further described below with reference to the embodiments:
[0080] Example 1
[0081] Prepare the metallization paste according to the formula shown in Table 1:
[0082] Table 1
[0083]
[0084] The metallization paste was prepared according to the following method:
[0085] Functional phase pretreatment: UV shielding powder and interfacial compatibilizer were added to anhydrous ethanol at a mass ratio of 100:1~10, stirred at 60℃ for 60 min, filtered, and dried at 150℃ for 2 h to obtain modified UV shielding powder; functional protective agent was added to organic solvent and ultrasonically dispersed for 30 min to obtain uniform protective agent dispersion.
[0086] Preparation of organic carrier: The resin was added to an organic solvent and stirred at 80°C until completely dissolved. After cooling to room temperature, thixotropic agent, anti-settling agent and glass powder were added and stirred at high speed (1200 rpm) for 50 min to obtain the organic carrier.
[0087] Preparation of functional slurry: Modified UV shielding powder was added to an organic carrier and stirred at high speed (1500 rpm) for 20 min. Then, protective agent dispersion was added and stirred for another 40 min. The slurry was then ground in a sand mill until the slurry D90 ≤ 6 μm to obtain the UV-ID resistant functional slurry.
[0088] Preparation of finished slurry: Slowly add the conductive phase to the UV-ID-resistant functional slurry, stir at low speed (300 rpm) for 30 min, degas under vacuum (vacuum degree ≥0.08 MPa) for 20 min, and adjust the slurry viscosity to 100 Pa・s (25℃, 10 rpm) to obtain the finished metallized slurry.
[0089] Comparative Example 1
[0090] Prepare the metallization paste according to the formula shown in Table 2:
[0091] Table 2
[0092]
[0093] The metallization paste was prepared according to the following method:
[0094] Preparation of organic carrier: The resin was added to an organic solvent and stirred at 80°C until completely dissolved. The mixture was then cooled to 60°C, and an interfacial compatibilizer was added and stirred for 20 min. After cooling to room temperature, a thixotropic agent, an anti-settling agent, and glass powder were added and stirred at high speed (1200 rpm) for 50 min to obtain the organic carrier.
[0095] Preparation of finished slurry: The conductive material is slowly added to the organic carrier, stirred at low speed (300 rpm) for 30 min, vacuum degassing (vacuum degree ≥0.08 MPa) for 20 min, and the viscosity of the slurry is adjusted to 100 Pa・s (25℃, 10 rpm) to obtain the finished metallized slurry.
[0096] The bare solar cell is prepared according to the following method:
[0097] For example Figure 1 Taking the TOPCon battery with the structure shown as an example, the finished metallization paste is screen-printed onto the TOPCon battery cell substrate, and electrodes are formed on the TOPCon battery substrate through a high-temperature co-sintering process to obtain the bare battery cell.
[0098] TOPCon solar cell blanks made using the finished metallization paste of Example 1 were used as the experimental group, and TOPCon solar cell blanks made using the finished metallization paste of Comparative Example 1 were used as the control group. The only difference between the experimental and control groups was the metallization paste used. Solar cell performance tests were conducted on both groups. Specifically, the performance of the solar cells before irradiation was tested, followed by irradiation of 15 kWh for 75 h. The performance of the solar cells after irradiation was then tested, and the rate of performance degradation after irradiation relative to the performance before irradiation was calculated.
[0099] The tested cell performance included Eta, Voc, Isc, and FF, and was specifically tested using the following methods:
[0100] I. Preparatory work before testing
[0101] 1. Battery cell cleaning, including:
[0102] Wipe the surface of the battery cells with ultrapure water, ethanol or isopropanol to remove fingerprints, dust and organic residues;
[0103] After drying the solar cells with nitrogen, let them stand for 10 minutes to avoid surface contamination affecting their optical properties.
[0104] 2. Electrode contact inspection, including
[0105] Use a four-wire probe (such as the Keithley 2400 series) to perform electrical measurements on the solar cells, ensuring that the contact resistance between the metal electrodes of the solar cells and the probe is <0.1Ω;
[0106] Use silver paste or spring probes to secure the battery cells and avoid pressure damage.
[0107] 3. Stabilization treatment, including:
[0108] Place the solar cells under standard lighting (1000W / m²). 2 Aging for 1 hour under light-induced degradation (LID) to eliminate light-induced degradation.
[0109] The temperature of the solar cells was maintained at 25℃±0.5℃ using a constant temperature stage to avoid the impact of thermal effects on carrier mobility.
[0110] 4. Equipment calibration, including:
[0111] The light source spectrum was calibrated using a standard reference cell to conform to the AM1.5G standard spectral conditions, with a calibration wavelength range of 300 nm to 1200 nm.
[0112] The irradiance uniformity deviation in the test area does not exceed ±2%, and the measurement error of the temperature sensor used is less than ±0.1℃.
[0113] II. Testing Equipment and Conditions
[0114] 1. Core equipment
[0115] IV tester: Keysight B2900A series, with a voltage resolution of 0.1mV and a current resolution of 0.1μA;
[0116] Solar simulator: Class AAA compliant, with selectable pulsed or steady-state light source (e.g., Wacom WXS-200S-20).
[0117] Temperature control console: Temperature regulation is achieved based on a thermoelectric cooling (TEC) module, with a control accuracy of ±0.2℃;
[0118] Spectral response instrument: equipped with a quantum efficiency (QE) testing system (such as Bentham PVE300).
[0119] 2. Standard Test Conditions (STC)
[0120] Irradiance: 1000 W / m 2 (AM1.5G standard spectrum);
[0121] Temperature: 25℃±1℃ (real-time monitoring via TEC module);
[0122] Light spot uniformity: The uniformity of the light spot covering the effective area of the battery is >95%.
[0123] III. Key Parameter Testing Procedures
[0124] 1. Conversion efficiency (Eta) and IV characteristics (Voc, Isc, FF) testing
[0125] Test equipment: solar simulator, IV tester and four-wire probe.
[0126] step:
[0127] (1) Sample placement: Place the battery cell in the center of the light spot of the simulator, and use a light shield to block the edge of the battery cell by 5mm to avoid light leakage at the edge;
[0128] (2) IV scan: Apply a scan voltage from -0.5V to Voc+0.5V through an IV tester, set the scan step size to 10 mV, and record the IV characteristic curve of the battery simultaneously;
[0129] (3) Parameter extraction: Extract the open-circuit voltage Voc (voltage when current = 0) and short-circuit current Isc (current when voltage = 0) from the IV curve;
[0130] (4) Calculation of power and fill factor: Calculate the maximum power point (Pmax = Vmpp×Impp) and fill factor FF = Pmax / (Voc×Isc) on the IV curve;
[0131] (5) Efficiency calculation: The conversion efficiency Eta = (Pmax / Pin) × 100% is calculated, where the incident light power Pin is calibrated by a calibrated standard cell.
[0132] The performance test results of the solar cells before and after irradiation in the experimental group are shown in Table 3:
[0133] Table 3
[0134]
[0135] The performance test results of the solar cells before and after irradiation are shown in Table 4:
[0136] Table 4
[0137]
[0138] As shown in Tables 3 and 4, under the same conditions, the UV-induced degradation test of the printed batteries showed that the performance degradation (especially Eta) of the experimental group batteries was significantly less than that of the control group. This indicates that the metallization paste of the present invention does indeed play a role in resisting UVID when applied to the battery cells, and the presence of functional substances in the paste significantly enhances the effect of resisting UVID.
[0139] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A solar cell, characterized in that, At least one electrode of the solar cell includes a functional material, which includes an ultraviolet shielding material, and the ultraviolet shielding material includes one or more of TiO2-SiO2 core-shell particles, ZnO-Al2O3 composite particles, and CeO2-doped TiO2 powder.
2. The solar cell according to claim 1, characterized in that, The D50 particle size of the ultraviolet shielding material is 30 nm to 250 nm.
3. The solar cell according to claim 1, characterized in that, The functional material accounts for 5% to 60% of the mass distribution in each of the electrodes.
4. The solar cell according to claim 1, characterized in that, The functional substance also includes a functional protective agent, which includes one or more of ultraviolet absorbers and ultraviolet light converting agents; The ultraviolet absorber includes one or more of the following: benzophenones, benzotriazoles, triazines, cyanoacrylates, salicylates, and polymeric ultraviolet absorbers; The ultraviolet conversion agent includes thermally activated delayed fluorescence organic conversion agents and rare earth phosphors; or, the ultraviolet conversion agent includes one or more of coumarin derivatives, naphthalimides, and perovskite quantum dots.
5. The solar cell according to claim 1, characterized in that, The electrode also includes an electrode body material, which is one or more of silver, silver-plated copper, silver-plated aluminum, and copper. The mass distribution of the electrode body material in each electrode is 40% to 95%.
6. The solar cell according to claim 1, characterized in that, The electrode substrate comprises a first silver powder and a second silver powder in a mass ratio of (6~9):
1. The first silver powder is a flake-shaped silver powder with a diameter of 3 μm~8 μm, and the second silver powder is a spherical silver powder with a D50 particle size of 0.5 μm~2 μm or a nano silver powder with a D50 particle size of 50 nm~200 nm.
7. A metallization paste, characterized in that, It includes the following components by mass percentage: Conductive material 70%~85%; The functional material is 2% to 8%, and the functional material includes ultraviolet shielding material, which includes one or more of TiO2-SiO2 core-shell particles, ZnO-Al2O3 composite particles, and CeO2-doped TiO2 powder. Organic carriers: 10%–22%; Interface compatibilizer 0.2%~0.8%; Additives: 0.3%~1.2%.
8. The metallizing paste according to claim 7, characterized in that, The D50 particle size of the ultraviolet shielding material is 30 nm to 250 nm.
9. The metallizing paste according to claim 7, characterized in that, The functional material includes an ultraviolet shielding material and a functional protective agent in a mass ratio of (15~25):1, wherein the functional protective agent includes one or more of ultraviolet absorbers and ultraviolet light-converting agents. The ultraviolet absorber includes one or more of the following: benzophenones, benzotriazoles, triazines, cyanoacrylates, salicylates, and polymeric ultraviolet absorbers; The ultraviolet conversion agent comprises a thermally activated delayed fluorescence organic conversion agent and a rare earth phosphor in a mass ratio of 1:(2~4); or, the ultraviolet conversion agent comprises one or more of coumarin derivatives, naphthalimides, and perovskite quantum dots.
10. The metallizing paste according to claim 7, characterized in that, The conductive material includes a first silver powder and a second silver powder in a mass ratio of (6~9):
1. The first silver powder is a flake-shaped silver powder with a diameter of 3 μm~8 μm, and the second silver powder is a spherical silver powder with a D50 particle size of 0.5 μm~2 μm or a nano silver powder with a D50 particle size of 50 nm~200 nm.
11. The metallizing paste according to claim 7, characterized in that, The organic carrier includes a resin and an organic solvent. The resin includes one or two of ethyl cellulose, acrylic resin and polyurethane resin, and the organic solvent includes one or two of terpineol, butyl carbitol and diethylene glycol monobutyl ether. The interface compatibilizer includes one or more of the following: silane coupling agent, titanate coupling agent, aminosilane, polysilazane derivative, or phosphorus-containing passivating agent. The additives include 0.1% to 0.8% thixotropic agent, 0.03% to 0.5% antisettling agent, and 0.1% to 1.0% glass powder.
12. A photovoltaic module, characterized in that, Including the solar cell as described in any one of claims 1 to 6.
13. A photovoltaic system, characterized in that, Including the photovoltaic module as described in claim 12.
